CARBON TAX PRACTICE IN THE TRANSPORTATION SECTOR : OPPORTUNITIES AND CHALLENGES IN INDONESIA - Indah Puspasari; Verani Carolina (LPPM STIE Muhammadiah Bandung, 2026)
This study examines the implementation of carbon taxation in Indonesia’s transport sector by analyzing its opportunities and challenges through a qualitative method using literature review and secondary data analysis. The research highlights the urgency of emission reduction, as transportation contributes approximately 23% of Indonesia’s total emissions, primarily from land-based vehicles. The methodology involves a comparative policy analysis and revenue projection using Holt's Linear Exponential Smoothing. The findings reveal that direct carbon taxes, as adopted in Sweden and Japan, provide greater revenue certainty but impose higher economic burdens. In contrast, emissions trading schemes (ETS), as implemented in South Korea and Singapore, are more flexible and market-driven but result in lower and less predictable revenues. Simulation results estimate that direct carbon taxation in the transport sector could generate approximately IDR 29.97 trillion between 2025 and 2030, while ETS may yield only around IDR 13.60 trillion. The study concludes that a phased, equitable, and well-targeted carbon tax policy—combined with strengthened institutional capacity, public education, and infrastructure development—can support Indonesia's climate goals while balancing social equity and economic growth.